Analisis Pemanfaatan Social Commerce bagi UMKM: Anteseden dan Konsekuen - Anissa Hakim Purwantini; Friztina Anisa (Kompartemen : Jurnal Ilmiah Akuntansi, 2018)
The purpose of this study is to investigate factors that influence social media usage among small and medium enterprises (SMEs) and the impact on financial and non-financial performance. Convenience sampling was used to collect data. The respondent in this study are owner of SME that use facebook and instagram on their business activities. Based on SEM-PLS analysis, this study revealed that interactivity, cost effectiveness, and trust was identified as factors that motivate the usage social media. Meanwhile, compatibility has no significant effect on social media usage. Social media usage has a strong positive impact on financial performance (sales) and non-financial performance of SMEs in terms of customer service, internal operations, and marketing. In addition, this study indicate that social media usage has no positive effects on perceived impact on innovation.Keywords: social media, SME, performance, inovation,social commerce